18th International Conference on Nuclear Engineering: Volume 6 2010
DOI: 10.1115/icone18-29331
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Considerations in Sustainable Development of Nuclear Power Plants in the United States

Abstract: Nuclear power generation has become an increasingly attractive alternative in the global power market due to growing demand for electric power, increasing global competition for fossil fuels, concern over greenhouse gas emissions and their potential impact on climate change, and the desire for energy independence. Nuclear energy plays an integral role in providing carbon free energy for sustainable development of global electric power generation. Assuring the protection of people and the environmental is a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…15,16,21 (1) Weight proportional to the inverse of the MAE, (2) weight proportional to the logarithm of the inverse of the MAE and (3) weight proportional to a Borda count-based ranking. 15 We consider the passive containment cooling system (PCCS) of AP1000 NPPs as case study 22 because (1) nuclear power is an energy option considered to reduce greenhouse gas emissions 23,24 and (2) it has been shown that the safety and reliability of NPPs are significantly influenced by changes of air temperature, precipitation, river flows, sea level, shoreline erosion, coastal storms, floods, heat waves and so on that affect cooling water supply. 2,8,[25][26][27] The proposed ensemble methods are used to aggregate the forecasts of the climate change models in order to assess the conditional functional failure probability (CFFP) of the PCCS by performing for an integrated probabilistic safety assessment conditional on climate projections 22,28 and to classify the temperature conditions that lead the PCCS to unexpected and dangerous scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,21 (1) Weight proportional to the inverse of the MAE, (2) weight proportional to the logarithm of the inverse of the MAE and (3) weight proportional to a Borda count-based ranking. 15 We consider the passive containment cooling system (PCCS) of AP1000 NPPs as case study 22 because (1) nuclear power is an energy option considered to reduce greenhouse gas emissions 23,24 and (2) it has been shown that the safety and reliability of NPPs are significantly influenced by changes of air temperature, precipitation, river flows, sea level, shoreline erosion, coastal storms, floods, heat waves and so on that affect cooling water supply. 2,8,[25][26][27] The proposed ensemble methods are used to aggregate the forecasts of the climate change models in order to assess the conditional functional failure probability (CFFP) of the PCCS by performing for an integrated probabilistic safety assessment conditional on climate projections 22,28 and to classify the temperature conditions that lead the PCCS to unexpected and dangerous scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…15,16,21 (1) Weight proportional to the inverse of the MAE, (2) weight proportional to the logarithm of the inverse of the MAE and (3) weight proportional to a Borda count–based ranking. 15 We consider the passive containment cooling system (PCCS) of AP1000 NPPs as case study 22 because (1) nuclear power is an energy option considered to reduce greenhouse gas emissions 23,24 and (2) it has been shown that the safety and reliability of NPPs are significantly influenced by changes of air temperature, precipitation, river flows, sea level, shoreline erosion, coastal storms, floods, heat waves and so on that affect cooling water supply. 2,8,2527…”
Section: Introductionmentioning
confidence: 99%